2021
DOI: 10.3389/fmicb.2021.736525
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Microbial Diversity and Volatile Flavor Compounds of Suan zuo rou, a Fermented Meat Product From Guizhou, China

Abstract: Suan zuo rou (SZR), a traditional fermented meat from Guizhou province, China, is loved by local people for its unique flavor and nutritional value. However, the microbial communities and related flavor characteristics of SZR from different regions of Guizhou are unclear. We studied the correlation between the microbial communities and the physicochemical properties and volatile flavor compounds (VFCs) of 15 SZR samples from three regions in Guizhou province. The microbial community structure of SZR was determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
10
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 75 publications
7
10
1
Order By: Relevance
“…The bacterial communities of the samples mainly included Firmicutes bacteria, and the proportion in each group was more than 95%, followed by Proteobacteria and other bacteria with a microbial abundance of less than 1% ( Figure 2 A). The results were consistent with those reported by Lv [ 12 ], and Wang [ 24 ]. Firmicutes accounted for the highest proportion in GXRS (99%), followed by GXJP (98%), GZCJ (98%), GZZY (97%), GZLB (96%), and HNXX (95%).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The bacterial communities of the samples mainly included Firmicutes bacteria, and the proportion in each group was more than 95%, followed by Proteobacteria and other bacteria with a microbial abundance of less than 1% ( Figure 2 A). The results were consistent with those reported by Lv [ 12 ], and Wang [ 24 ]. Firmicutes accounted for the highest proportion in GXRS (99%), followed by GXJP (98%), GZCJ (98%), GZZY (97%), GZLB (96%), and HNXX (95%).…”
Section: Resultssupporting
confidence: 93%
“…1-octen-3-ol is a common unsaturated alcohol in fermented meat products with a low odor threshold that is oxidized by arachidonic acid and has a mushroom and flower scent [ 36 ]. In this study, 1-octen-3-ol was found in all samples, but its content was high in GZZY, which was consistent with the results of Wang [ 24 ]. Previous studies have reported that 1-hexanol and 1-octen-3-ol are one of the primary flavor components of Dong sour meat [ 19 , 24 ].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Rahnella , Lachnospiraceae AC2044 group , Ruminococcaceae UCG 005 , Unspecified Lachnospiraceae , Rikenellaceae RC9 gut group , and Ruminococcaceae UCG 010 showed extremely positive patterns, while Vibrio , Myroides , Morganella , Psychrobacter , and Arthrobacter showed a highly significant co-occurrence pattern. In our study, these microbes of Vibrio , Myroides , and Psychrobacter , regarded as strengthening the aroma profile of meat, showed microbial co-occurrence network results similar to those observed in previous studies ( Hu et al, 2020 ; Wang et al, 2021 ). Correlation analysis of bacterial genera showed that Lactobacillus had weak and negative correlations with almost all other bacterial genera except for Macrococcus , Leuconostoc , and Weissella .…”
Section: Resultssupporting
confidence: 90%
“…The abundant genes about amino acid metabolism seem to be helpful for the development of fermented sausage in our results. The different bacterial genera related to lipid metabolism could make up an important component of the volatile composition in smoked horsemeat sausages ( Wang et al, 2021 ). These tendencies make sense in fermentation process of smoked horsemeat sausages.…”
Section: Resultsmentioning
confidence: 99%